Types of Illocutionary Act Used by Raditya Dika in Sucrd 2016 - Istigfa Augia; Refnaldi Refnaldi (Universitas Negeri Padang, 2022)
This study aims to reveal the types of illocutionary act used by Raditya Dika in his You-tube video entitled SUCRD 2016. The source of data is script video Raditya Dika stand-up comedy entitled SUCRD 2016. The data in this study are all the punchline that found by Raditya Dika. Searle theory is applied in this study using descriptive to analyze the data. The results of this study shows that in delivering punchline, Raditya Dika used four types of illocutionary act. The most illocutionary types used by Raditya Dika is representative which 90 data (76,27%) from 118 total punchline. Commisive is the type that lowest types that used by Raditya Dika with 1 data found (0,84%) from total 118 punchline. Declarative is the rare types used by Raditya Dika in his stand-up comedy